MANAJEMEN BIMBINGAN DAN KONSELING PREVENTIF DALAM KENAKALAN REMAJA - Wanda Mahmudah Nabillah; Ririn Inayatul Mahfudloh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Juvenile delinquency in the school environment is one of the educational problems that can influence students’ social, emotional, and academic development. Various forms of deviant behavior such as truancy, lateness, smoking, violations of school rules, and irresponsible use of social media indicate the need for systematic preventive efforts through guidance and counseling services. This study aims to analyze the management of preventive guidance and counseling in preventing juvenile delinquency at Madrasah Aliyah Al Muniroh ujungpangkah Gresik. This research employed a descriptive qualitative approach with a case study design. The research subjects consisted of the school principal, guidance and counseling teachers, and students. Data were collected through observation, interviews, and documentation. The results of the study show that the management of preventive guidance and counseling is implemented through the stages of program planning, implementation, and evaluation. Program planning is prepared based on students’ needs analysis obtained from records of rule violations and observations of students’ behavior. The implementation of services includes classroom guidance, group guidance, individual counseling, and character strengthening integrated with religious values. The implementation of these preventive services is able to increase students’ understanding of the impacts of juvenile delinquency, strengthen self-control, and foster moral awareness so that the potential for juvenile delinquency can be minimized within the school environment.